The Cell Origin and Role of Osteoclastogenesis and Osteoblastogenesis in Vascular Calcification - Jiang, Wenhong; Zhang, Zhanman; Li, Yaodong; Chen, Chuanzhen; Yang, Han; Lin, Qiuning; Hu, Ming; Qin, Xiao (Frontiers in Cardiovascular Medicine, 2021)
Arterial calcification refers to the abnormal deposition of calcium salts in the arterial wall, which results in vessel lumen stenosis and vascular remodeling. Studies increasingly show that arterial calcification is a cell mediated, reversible and active regulated process similar to physiological bone mineralization. The osteoblasts and chondrocytes-like cells are present in large numbers in the calcified lesions, and express osteogenic transcription factor and bone matrix proteins that are known to initiate and promote arterial calcification. In addition, osteoclast-like cells have also been detected in calcified arterial walls wherein they possibly inhibit vascular calcification, similar to the catabolic process of bone mineral resorption. Therefore, tilting the balance between osteoblast-like and osteoclast-like cells to the latter maybe a promising therapeutic strategy against vascular calcification. In this review, we have summarized the current findings on the origin and functions of osteoblast-like and osteoclast-like cells in the development and progression of vascular progression, and explored novel therapeutic possibilities.